The Development of Disaster Awareness in Primary Schools to Promote Awareness among Kelompok Kerja Guru (Teacher Working Group) 03 of Silo Sub-district in Jember - Zetti Finali; Muh Zulfatul A'la; Agustiningsih Agustiningsih (LP2M Universitas Jember, 2019)
This project aims to raise awareness in the Kelompok Kerja Guru or KKG (Teacher Working Group) 03 Silo sub-district, Jember by developing Disaster Awareness in Primary Schools. Efforts to boost awareness are done through implementing training in the preparation of disaster-based learning tools and actions that must be taken by the teachers if a disaster occurs. The methods used in this service were (1) discussion on preparedness efforts and the level of teacher's awareness for disasters, (2) teachers training on the concept of disaster awareness in primary schools in the KKG 03 using modules, and (3) teachers assistance in transferring knowledge to students.